Gender disparities in a psychiatric department in Tunisia. (1st June 2022) - Bergaoui, E.; Zrelli, M.; Staali, N.; Moalla, M.; Lansari, R.; Larnaout, A.; Melki, W.
Abstract : Introduction: Gender disparities exist regarding prevalence, symptomatology and risk factors of mental disorders. In Tunisia, there is only one hospital dedicated entirely to mental health which is Razi hospital. Objectives: The aim of the present study was to assess gender based mental health disparities in a psychiatric department and its related factors. Methods: A cross sectional and comparative survey was conducted between March and April 2021 in the department of psychiatry D of Razi Hospital including 70 patients with a sex ratio= 1. Results: The participants were aged between 17 and 68. Men had higher rate of celibacy: 80% of men against 48.57% of women (p=0.009). A total of 11.42% of women were illiterate against 2.85% of men, 48% of men were unemployed against 62.85% of women. There was a significant difference between gender and use of cigarettes, cannabis and alcohol (p<0.001). The diagnosis was mood disorders for 35.42% of women and 17.14% of men and schizophrenia for 57.14% of women and 77.14% of men. Gender and modality of hospitalization were significantly associated (p=0.046): 14% of women were involuntary hospitalized against 40% of men. Time between symptoms onset and consulting is 3.5 years (±5.67) for women and 1.77 (±4.75) for men. The mean number of admissions for women is 1.59 and for men 4.2 (p=0.009). Conclusions: Onset of mental disorders for women is 3 to 4 years later than men. They have better premorbid functionning and better social networks.Gender disparities are not only determined biologically but also socially. Disclosure: No significant relationships.